Pemberdayaan Masyarakat Melalui Pemanfaatan Gula Merah Dari Nira Kelapa - Yendri Novika Putri; Warto Warto (ICODEV: Indonesian Community Development Journal, 2021)
Brown sugar is one of the artificial sweetener products made from coconut sap water and has long been produced by the Indonesian people. Brown sugar is also an alternative food sweetener that is the main source of livelihood for some rural Kalijeruk communities. The purpose of this study was to determine the productivity and contribution of brown sugar to people’s incomes and the utilization of coconut tree resources. Calculation of productivity and income contribution of the Kalijeruk village community because during a pandemic like today, many people have lost their jobs so as to cope with the economy. Some people take advantage of the natural resources of coconut trees in the community by making brown sugar and market snacks. The method used by the author is the direct observation method of making brown sugar from tapping or tapping to making and packaging brown sugar so that sales generate quite a lot of income, from that the packaging is made varied.